Population and Habitat Suitability Index Model of Bali Starling (Leucopsar rothschildi) in West Bali National Park - Fadlan Pramatana; Jarwadi Budi Hernowo; Lilik Budi Prasetyo (Jurnal Sylva Lestari, 2022)
Bali starling (Leucopsar rothschildi) is categorized as an endangered species based on the International Union for Conservation of Nature and Natural Resources (IUCN) red list. Thus, preventing this species from extinction becomes very crucial. One of the most important activities for this purpose is a soft release method to avoid birds' mortality, which has been done in West Bali National Park (WBNP). However, this method creates the dependency of birds to the artificial treatment and may affect the distribution of Bali starling. Therefore, this study aimed to analyze the population and habitat and create a habitat suitability index model for Bali starling in WBNP. Data were obtained by surveying the Bali starling population, including the number of individuals, distribution, age structure, sex ratio, natality, and mortality. Vegetation analysis was also conducted to determine habitat conditions. Finally, map interpretation data was used to develop a suitable habitat model for Bali starling in WBNP. The results showed that 63 Bali starling were found near the resort office, bird release sites, and binding bird cages. It indicated that the habitat of Bali starling has shifted from the soft release site. The habitat suitability index model of Bali starling in WBNP was Y = 17.145 + 6.640PC1 - 4.055PC2, showing the selected variables only give a moderate determination coefficient (R2 = 40.9%). The artificial treatment created by the WBNP authority seems to be another great factor influencing the existence and distribution of Bali starling in WBNP. It was also indicated that Bali starling could breed in the WBNP, but it tends to have a shifting habitat in the wild. Keywords: Bali starling, Geographic information system, Habitat suitability, Population